Soil bacterial community structure and functioning in a long-term conservation agriculture experiment under semi-arid rainfed production system - Pratibha, G.; Manjunath, M.; Raju, B. M. K.; Srinivas, I.; Rao, K. V.; Shanker, Arun K.; Prasad, J. V. N. S.; Rao, M. Srinivasa; Kundu, Sumanta; Indoria, A. K.; Kumar, Upendra; Rao, K. Srinivasa; et al. (Frontiers in Microbiology, 2023)
Soil microbial communities are important drivers of biogeochemical cycling of nutrients, organic matter decomposition, soil organic carbon and Greenhouse gas emissions (GHGs: CO2, N2O, and CH4) and are influenced by crop and soil management practices. The knowledge on the impact of conservation agriculture (CA) on soil bacterial diversity, nutrient availability and GHG emissions in semi-arid regions under rainfed conditions is vital to develop sustainable agricultural practices but such information has not been systemically documented. Hence, studies were conducted for 10 years in rainfed pigeonpea (Cajanus cajan L.) - castor bean (Ricinus communis L.) cropping system under semi-arid conditions to assess the effects of tillage and crop residue levels on the soil bacterial diversity, enzyme activity (dehydrogenase, urease, acid phosphatase, and alkaline phosphatase), GHG emissions and soil available nutrients (Nitrogen, phosphorus and potassium). Sequencing of soil DNA through Illumina Hiseq based 16S r RNA amplicon sequencing technology has revealed that bacterial community responded to both tillage and residue levels. The relative abundance of Actinobacteria in terms of Operational Taxonomic Unit (OTUs) at phyla, class as well as genera level were higher in CA (NTR1: No Tillage + 10 cm anchored residue and NTR2 NT + 30 cm anchored residue) over CT (conventional tillage without crop residues). CA resulted in higher enzyme activities (dehydrogenase, urease, acid phosphatase, and alkaline phosphatase) and reduction in GHG emissions over CT. CA recorded 34% higher and 3% lower OC, as compared to CT, and CTR1 respectively. CA recorded 10%, 34 % and 26 % higher available nitrogen, phosphorus and potassium over CT and CTR1 respectively. NTR1 recorded 25 and 38% lower N2O emissions as compared to CTR1 and CTR2 respectively. Whereas only NT recorded 12% higher N2O emissions as compared to CT. Overall, the results of the study indicate that, CA improves the relative abundance of soil bacterial communities, nutrient availability, enzyme activities and may help to contribute to the mitigation of climate change, and sustainability in rainfed conditions.